2012
DOI: 10.1111/j.1462-2920.2012.02799.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distance and pH drive bacterial distribution in alkaline lake sediments across Tibetan Plateau

Abstract: Continent-scale biogeography has been extensively studied in soils and marine systems, but little is known about biogeographical patterns in non-marine sediments. We used barcode pyrosequencing to quantify the effects of local geochemical properties and geographic distance for bacterial community structure and membership, using sediment samples from 15 lakes on the Tibetan Plateau (4–1670 km apart). Bacterial communities were surprisingly diverse, and distinct from soil communities. Four of 26 phyla detected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
249
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(306 citation statements)
references
References 46 publications
48
249
9
Order By: Relevance
“…However, for larger spatial extents similar to those we considered here, former reports indicate that the bacterial distance-decay relationships range from significant in lake surface sediments across the Tibetan Plateau (Xiong et al, 2012) to nonsignificant in North America soils (Fierer and Jackson, 2006). These results collectively suggest that the rate of distancedecay in bacteria shows strong context-dependency, potentially driven by among-habitat variation in the degree of environmental spatial autocorrelation and in the degree of dispersal limitation.…”
Section: Phylogenetic Signal Varies With Phylogenetic Distancesupporting
confidence: 76%
“…However, for larger spatial extents similar to those we considered here, former reports indicate that the bacterial distance-decay relationships range from significant in lake surface sediments across the Tibetan Plateau (Xiong et al, 2012) to nonsignificant in North America soils (Fierer and Jackson, 2006). These results collectively suggest that the rate of distancedecay in bacteria shows strong context-dependency, potentially driven by among-habitat variation in the degree of environmental spatial autocorrelation and in the degree of dispersal limitation.…”
Section: Phylogenetic Signal Varies With Phylogenetic Distancesupporting
confidence: 76%
“…Recent studies have shown that shifts in the structure of bacterial communities can be associated with changes in a number of soil physicochemistry including soil texture (Sessitsch et al 2001;Kim et al 2013), soil pH (Mannisto et al 2007;Lauber et al 2008;Xiong et al 2012), soil moisture , temperature (Lipson 2007), and soil nitrogen (Frey et al 2004;Nilsson et al 2007). From the baseband to the top of the mountain, environmental factors (including soil physicochemistry, plant and climate) change sharply (Korner 2007), indicating that bacterial distributions may exhibit differently owe to variations of environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…(5 -CCGTCAATTCMTTTRAGTTT-3 ) [22] were used to amplify the V4-V5 region of the bacterial 16S rRNA gene. DNA amplicons were separated by electrophoresis on a 2% (w/v) agarose gel and recovered using an AxyPrep DNA Gel Extraction Kit (Axygen Ltd., Hangzhou City, China).…”
Section: High-throughput Sequencingmentioning
confidence: 99%